A Historical Approach to Understanding Differentiation of RYB vs RGB - Patron, Ernesto Carlos Pujazon; Zegarra, Maria Alexandra Guerrero; Elias, Jose Domingo (Journal of Visual Art and Design, 2024)
This article defines the roles of colors and presents their historical development as a fundamental means of expression within artwork. It also introduces color theorists and practices, including the mixing of pigments, a necessary technique for artists-designers in creating tangible results. Modern artists-designers have used these theorists to express themselves in producing an aesthetic experience in the viewer through their artwork, starting with Sir Isaac Newton’s light-spectrum experiments using a glass prism and a beam of white light, and continuing through Johannes Itten’s color-wheel and creative color-matching exercises. This article objective defines the significance of color, its historical development on the basis of earlier perceptual theorists’ findings that color acquires dimension and meaning in response to cultural-historical context or psychological realities. As a result, this paper also explores how color affects our emotions, our psychic and spiritual manifestations. This psychic-spiritual manifestation is revealed through a process of visual perception and experimenting with color and its symbolic meaning. Artists such as Seurat, Munch, Kandinsky, Paul Klee, Josef Albers, Picasso, Joan Miro, or Mark Rothko demonstrated the expressive power of color-pigment. The authors hope that this paper will bring significant discussion, awareness, will assist general readers and academic researchers and truly advance knowledge.